Analysis of Dispute Resolution Related to Royalties and Song Copyright (Case Study of Ahmad Dhani's Feud with Once Mekel) - Hans Daniel Felix Tairas; Steven Cai Lee Phua (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
Dewa 19 is a band that was founded in 1986. With the works he has created, Dewa 19 is the best band in Indonesia. But lately there has been controversy because the former vocalist of Dewa 19, namely Once Mekel, performed Dewa 19’s song without permission from Ahmad Dhani (as the founder of the band Dewa 19). In addition, it is alleged that Once Mekel never paid royalties for Dewa 19 songs he performed. The controversy is also caused because there are no clear regulations regarding the collection of royalties and the protection of copyrights for musical works and songs. For Royalty payments there is also an institution whose job is to collect payments collectively to someone who performs a registered song. But until now there has been no clear arrangement regarding the payment. This research uses normative research methods to examine problems by looking at statutory provisions, where normative legal research has characteristics as library research by focusing on Law Number 28 of 2014 concerning Copyright.